The Role Of Teachers In Improving Learning Interest In Civics Education Learning Of Grade IV Students Of Nusukan Barat State Elementary School - Afni Arifatul Hidayah; Aisha Azmi Zahran; Ananda Ayu Rahmadhani; Rawanoko, Endrise Septina (Academic Solution Publisher, 2024)
Low student interest in citizenship education (civics education) is one of the problems often encountered in schools. This condition is influenced by various factors, including teacher teaching methods and student motivation. This study aims to describe the role of teachers in fostering students' interest in learning Civics Education in grade IV at ELEMENTARY SCHOOL Nusukan Barat, as well as the factors that influence this interest. This research uses a qualitative approach. Data collection techniques included observation during learning, semi-structured interviews with respondents from the fourth-grade teacher of ELEMENTARY SCHOOL Nusukan Barat, and documentation studies conducted in the fourth-grade classroom of ELEMENTARY SCHOOL Nusukan Barat. The results showed that the teacher's role as a facilitator, motivator, informator, and classroom manager has a significant influence in increasing students' interest in learning. In addition, there are supporting factors such as teacher creativity and competence, supportive school programs, and good communication between teachers and students. However, there are also inhibiting factors such as limited learning time, students' dislike of the subject, and lack of support from parents at home. Therefore, the active role of teachers in the learning process and classroom management is very important in fostering students' interest in learning. It is recommended that teachers continue to increase creativity in teaching and involve parents to support learning at home so that students' interest in learning Civics can be improved optimally.